Management of Nonpuerperal Uterine Inversion Using a Combined Vaginal and Abdominal Approach - Ferid A. Abubeker; Mulugeta Misgina; Ahmed Ebabu; Eyerusalem Fekade; Biruck Gashawbeza (Hindawi Limited, 2020)
Introduction. Nonpuerperal uterine inversion is an extremely rare clinical condition. As such, some cases will have to be managed without prior experience. Clinicians must have a high index of suspicion to make the diagnosis and a clear understanding of the principles of recommended surgical techniques. Here, we report a case of nonpuerperal uterine inversion managed using a combined vaginal and abdominal approach. Case Presentation. A 70-year-old postmenopausal woman presented with profuse vaginal bleeding and protruding mass per vagina. Examination showed a solitary globular mass attached to an inverted uterus. A clinical diagnosis of nonpuerperal uterine inversion was made. A vaginal approach was used to first remove the mass followed by an abdominal approach to reposition the uterus using the Haultain procedure. Subsequently, total abdominal hysterectomy with bilateral salpingo-oophorectomy was done without complication. Histologic examination showed myoma with adenomyosis. Conclusion. Advanced imaging techniques such as 3D power Doppler and MRI have signature signs to confirm the clinical diagnosis of uterine inversion. Short of these diagnostic modalities, however, carefully conducted clinical examination including examination under anesthesia, and pelvic ultrasonography can be valuable tools to reach at a diagnosis. A combined vaginal and abdominal surgical approach can facilitate repositioning and/or hysterectomy when there is a large protruding vaginal mass.